2012
DOI: 10.1038/cmi.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 protein inhibits LPS stimulation on monocyte-derived dendritic cells

Abstract: ST2 protein is a soluble splicing variant of ST2L protein, which is the receptor for interleukin-33 (IL-33). Previously, we reported that soluble ST2 suppressed the signal transduction of lipopolysaccharide (LPS) and cytokine production in monocytic cells. To investigate whether or not this inhibitory effect occurs in dendritic cells, which are the key players in innate and adaptive immunity, human monocyte-derived dendritic cells were pre-treated with soluble ST2 protein before LPS stimulation. Although solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
1
13
0
2
Order By: Relevance
“…Pre-treatment with IL-33 also did not influence the ST2-induced promotion of cell proliferation (data not shown) [17] . At present, it appears that ST2 itself may be responsible for the growth enhancement of NIH-3T3 cells, via an as-yet-unknown cell surface receptor for ST2 or via direct internalization as reported previously [16] . Indeed, the unexpectedly remarkable effect of shRNA-resistant ST2 ( Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Pre-treatment with IL-33 also did not influence the ST2-induced promotion of cell proliferation (data not shown) [17] . At present, it appears that ST2 itself may be responsible for the growth enhancement of NIH-3T3 cells, via an as-yet-unknown cell surface receptor for ST2 or via direct internalization as reported previously [16] . Indeed, the unexpectedly remarkable effect of shRNA-resistant ST2 ( Fig.…”
Section: Discussionsupporting
confidence: 68%
“…However, the spectrum of diseases that are accompanied by high ST2 levels in the serum and body fluids is too broad to be explained merely by immunological function(s) of the ST2 gene products. In fact, we found that ST2 suppresses colony formation of T98G glioblastoma cell line in soft agar [15] , and that the ST2 is directly internalized into dendritic cells [16] , and both these findings suggest that ST2 has a unique function other than the sequestration of IL-33 [5] .…”
Section: Introductionmentioning
confidence: 68%
“…39 The soluble form of the receptor, sST2, acts as a decoy receptor blocking IL-33 signaling 25,40 and inhibiting lipopolysaccharide-induced cytokine production. 41 Previous observations in other models of inflammation have shown IL-33 to be either pro-inflammatory or anti-inflammatory depending on the disease entity. A pro-inflammatory role for IL-33 was found in respiratory syncytial virus infection, 42 and neutralizing antibodies against ST2 attenuated lung inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…RAW264.7 macrophages (1 × 10 6 cells) were pre-incubated with tested samples or PBS for 12 h at 37 °C following LPS stimulation (1 μg mL −1 ) for 24 h. After stimulation with LPS, the cells were washed three times with PBS and then harvested with 0.25% trypsin (Gibco, Carlsbad, CA, USA). TLR4 protein on the cell surface was analyzed by fluorescence activated cell sorting (FACS) with anti-TLR4-PE by a slight modification of previously described methods [ 27 ]. Briefly, the cells were washed three times and resuspended in FACS buffer (PBS containing 1% BSA).…”
Section: Methodsmentioning
confidence: 99%